2019
DOI: 10.1002/cbdv.201900431
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Aminothiazole Derivatives as Hedgehog Pathway Inhibitors

Abstract: A series of aminothiazole derivatives bearing the benzimidazole moiety were synthesized and evaluated in Gli luciferase reporter assays. Lead optimization led to the discovery of potent hedgehog pathway antagonist 18 (2-[3-(1H-benzimidazol-2-yl)-4-chloroanilino]-N-[4-(trifluoromethyl)phenyl]-1,3-thiazole-4-carboxamide), with IC 50 values in nanomolar range. The molecular basis ascribed to hindering sonic hedgehog-driven Smoothened (Smo) localization within the primary cilium (PC). Moreover, compound 18 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The benzimidazole-thiazole hybrids exhibited considerable antiproliferative activity, [49][50][51][52] and among them, hybrid 19 (Figure 4; IC 50 : 2.4-12.0 µM, MTT assay) was active against HT-29, DU145, A549, and MDA-MB-231 cancer cell lines and the activity was comparable to that of doxorubicin (IC 50 : 1.8 µM) against A549 cells. [52] The SAR indicated that the introduction of hydrazine into thiazole moiety was permitted and hybrid 20 (IC 50 : 6.3 µM, MTT assay) was not inferior to erlotinib (IC 50 : 4.2 µM) against MCF-7 cells.…”
Section: Benzimidazole-sulfone/ Sulfonamide Hybridsmentioning
confidence: 99%
“…The benzimidazole-thiazole hybrids exhibited considerable antiproliferative activity, [49][50][51][52] and among them, hybrid 19 (Figure 4; IC 50 : 2.4-12.0 µM, MTT assay) was active against HT-29, DU145, A549, and MDA-MB-231 cancer cell lines and the activity was comparable to that of doxorubicin (IC 50 : 1.8 µM) against A549 cells. [52] The SAR indicated that the introduction of hydrazine into thiazole moiety was permitted and hybrid 20 (IC 50 : 6.3 µM, MTT assay) was not inferior to erlotinib (IC 50 : 4.2 µM) against MCF-7 cells.…”
Section: Benzimidazole-sulfone/ Sulfonamide Hybridsmentioning
confidence: 99%